Civic Religion after Trent: Confraternities and Medici State Building in Early Modern Livorno - Terpstra, Nicholas (Confraternitas, 2022)
When building the new city of Livorno, the Medici were concerned as much with social and religious life as with buildings, walls, and warehouses. They drew on traditional civic religious forms, and above all confraternities, in order to advance Catholic worship while also seeking to limit Roman intervention and maintain sufficient local agency so as to allow some degree of Jewish, Muslim, and Orthodox worship in the city. We can distinguish three groups of brotherhoods by origin and function in the first century of Livorno’s expansion from the late sixteenth to the late seventeenth centuries: i) Older and existing confraternities that had gathered the local fishermen and the earliest settlers until about 1590; ii) Confraternities founded between the 1590s and the 1630s, often with direct Medici or more general Florentine influence, and focused on meeting cultic and charitable needs; and iii) Confraternities established from the 1630s to the 1670s to fulfill these needs while also organizing activities that responded to challenges and opportunities of Livorno’s particular location. Florentine civic religious models allowed the Medici to build a vibrant Catholic social framework in Livorno while keeping Tridentine ecclesiastical forces at bay, at least until the coming of the more traditionally pious Grand Duke Cosimo III in 1670.